The Use Of The Gasing Method To Improve Learning Outcomes Of Mathematics - Marlina Stepani Manurung; Yuyun Bahtiar; Luluk Choirun Nisak Nur; Ulfa Wulan Agustina (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study aims to improve the learning outcomes of Mathematics on the main material of calculating the circumference of flat shapes using the gasing method (easy, fun, enjoyable) for students of class III Elementary Schools Public 102007 Matapao in the 2024-2025 academic year. In this classroom action research, 22 students of class III Elementary Schools Public 102007 Matapo in the 2024-2025 academic year were the subjects of the recipients of the action, while the class 3 teacher was the subject of the perpetrator, the subject of the data source was the Principal. Data collection was carried out through test techniques, this classroom action research was carried out in two cycles, each cycle consisting of activities: planning, action, testing, and reflection. The results of this study prove that the use of the gasing method (easy, fun, enjoyable) can improve student learning outcomes in Mathematics subjects on the material of calculating the circumference of flat shapes for students of class III Elementary Schools Public 102007 Matapao in the 2024-2025 academic year. Judging from the average value of students' Mathematics learning outcomes that increased, namely before the action (pre-cycle) (71.68) in cycle I (73.04) and in cycle II (80.22). In addition, the percentage of student learning outcomes completion, namely before the action (45.45%), in cycle I (7.72%), and in cycle II was (90.90%).